2015
DOI: 10.1186/s40152-015-0032-y
|View full text |Cite
|
Sign up to set email alerts
|

Towards adaptive co-management of small-scale fisheries in Uruguay and Brazil: lessons from using Ostrom’s design principles

Abstract: The literature on commons has established the validity and significance of Elinor Ostrom's design principles for collective action. Can these principles be used to guide policies and initiatives towards adaptive co-management? We analyze this idea by using two case studies, Piriápolis (Uruguay) and Paraty (Brazil). Both cases are small-scale fisheries, and both have been experiencing a social-ecological crisis in a context of prevailing top-down government management. However, there are signs that government p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0
14

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(81 citation statements)
references
References 51 publications
4
57
0
14
Order By: Relevance
“…While it is clear that what the details of "co-management" means is still not fully shared, it is still notable that there is significant interest in attempting to take action at a local level to address the problems each community faces, and they all face in common. This approach to using co-management is not only seen to have potential by Colombian stakeholders, but also in other Latin American countries that face similar issues due to fisheries crises, such as Mexico (Salas et al 2015), Costa Rica (Solís et al 2015), Brazil (Futemma and Seixas 2008), Uruguay (Trimble and Berkes 2015), and Chile (Marin and Berkes 2010). Even in Colombia, there are examples of cases that have tried participatory management with varying degrees of success (Beardon 2008;Delgado et al 2010;Navia et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…While it is clear that what the details of "co-management" means is still not fully shared, it is still notable that there is significant interest in attempting to take action at a local level to address the problems each community faces, and they all face in common. This approach to using co-management is not only seen to have potential by Colombian stakeholders, but also in other Latin American countries that face similar issues due to fisheries crises, such as Mexico (Salas et al 2015), Costa Rica (Solís et al 2015), Brazil (Futemma and Seixas 2008), Uruguay (Trimble and Berkes 2015), and Chile (Marin and Berkes 2010). Even in Colombia, there are examples of cases that have tried participatory management with varying degrees of success (Beardon 2008;Delgado et al 2010;Navia et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Cox et al (2010) also mentioned the limitations of Ostrom's principles in considering user community's internal power play. In general, Ostrom's design principles may be used as a guidelines to understand the sufficiency of incentives and maturity of social capital at community level; mostly through appraisal of internal institutional aspects, and without considering whole gamut of external factors (Yandle 2003(Yandle , 2008Cox et al 2010;Trimble and Berkes 2015). Thus, we need to consider any external force, like non-authorized users' interest in the FPA, which may hold potential opportunity or threat for the successful continuation of the FPA model.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been observed that the presence of the NGO created hopes among general villagers and involving parties in settlement of disputes and disagreements in more credible, smooth and less expensive ways. In the sphere of co-management, many studies have concluded that different levels of competence and distributed decision-making along with multiple stakeholders with multiple relationships (Carlsson and Berkes 2005;Marín and Berkes 2010;Trimble and Berkes 2015).…”
Section: Distinct Features Of the Daudkandi Modelmentioning
confidence: 99%
“…There is abundant literature on fisherfolk organisations such as cooperatives (Jentoft 1985and 1986, Hannesson 1988, Meynell 1984and 1990, on co-management (Brown and Pomeroy 1999, Pomeroy et al 2004, Pomeroy and RiveraGuieb 2005 and on adaptive co-management (Armitage et al 2007, Trimble andBerkes 2015). These provide much information from both conceptual and empirical Fig.…”
Section: Conceptsmentioning
confidence: 99%